The complete chloroplast genome sequence of Centaurea cyanus (Asteraceae). Issue 3 (4th March 2023) - Zhang, NingYun; Xie, Peng; Huang, Kerui; Yin, Hanbin; Mo, Ping; Wang, Yun
Abstract: Centaurea cyanus has been a weed in farmland for a long time. In this study, the chloroplast genome of C. cyanus was sequenced to establish the phylogenetic relationship between its genomic characteristics and other related species. The chloroplast gene structure of C. cyanus is a circular molecule with a length of 152, 433 bp, including a large single-copy (LSC) region of 83, 464 bp, a small single-copy (SSC) region of 18, 545 bp, and a pair of inverted repeats sequences (IRs) region of 25, 212 bp. The whole genome contains 130 genes, including 86 protein-coding genes, 36 tRNA genes, and eight rRNA genes. Phylogenetic analysis showed that C. cyanus is close to Carthamus. tinctorius, C. tinctorius, C. diffusa, and C. maculosa, and all of them were in one clade. This study provides genetic resource information for the further study of Centaurea .